Population-Based Surveillance of Neisseria meningitidis Antimicrobial Resistance in the United States. (14th August 2015) - Harcourt, Brian H.; Anderson, Raydel D.; Wu, Henry M.; Cohn, Amanda C.; MacNeil, Jessica R.; Taylor, Thomas H.; Wang, Xin; Clark, Thomas A.; Messonnier, Nancy E.; Mayer, Leonard W.
Abstract : Isolates of Neisseria meningitidis collected in 2004, 2008, 2010, and 2011 from an active population-based surveillance system in the United States were tested for susceptibility to antimicrobials used for treatment and chemoprophylaxis of meningococcal disease. Susceptibility remains high and stable. Abstract: Background.  Antimicrobial treatment and chemoprophylaxis of patients and their close contacts is critical to reduce the morbidity and mortality and prevent secondary cases of meningococcal disease. Through the 1990's, the prevalence of antimicrobial resistance to commonly used antimicrobials among Neisseria meningitidis was low in the United States. Susceptibility testing was performed to ascertain whether the proportions of isolates with reduced susceptibility to antimicrobials commonly used for N meningitidis have increased since 2004 in the United States. Methods.  Antimicrobial susceptibility testing was performed by broth microdilution on 466 isolates of N meningitidis collected in 2004, 2008, 2010, and 2011 from an active, population-based surveillance system for susceptibility to ceftriaxone, ciprofloxacin, penicillin G, rifampin, and azithromycin. The molecular mechanism of reduced susceptibility was investigated for isolates with intermediate or resistant phenotypes. Results.  All isolates were susceptible to ceftriaxone and azithromycin, 10.3% were penicillin G intermediate (range, 8% in 2008–16.7% in 2010), and <1% were ciprofloxacin, rifampin, or penicillin G resistant. Of the penicillin G intermediate or resistant isolates, 63% contained mutations in the penA gene associated with reduced susceptibility to penicillin G. All ciprofloxacin-resistant isolates contained mutations in the gyrA gene associated with reduced susceptibility. Conclusions.  Resistance of N meningitidis to antimicrobials used for empirical treatment of meningitis in the United States has not been detected, and resistance to penicillin G and chemoprophylaxis agents remains uncommon. Therapeutic agent recommendations remain valid. Although periodic surveillance is warranted to monitor trends in susceptibility, routine clinical testing may be of little use.